Assessment of the outcome of fracture proximal humerus transdeltoid versus deltopectoral approach with PHILOS - Anand, Rajeev; Dwivedi, Amit; Agarwal, Apoorve; Shah, Fenil (International Journal of Research in Orthopaedics, 2020)
Introduction: Fracture proximal humerus accounts for 4 percent of all fractures. Out of all the humerus fractures, proximal fractures accounts for 26%. According to the Neer’s classification, 2, 3- and 4-part fracture are difficult to achieve stable fixation. In this study, we want to assess whether the different surgical approach, deltopectoral and transdeltoid approach, used for the stabilization of the fracture proximal humerus effects on the outcome of the surgery. Method: A total of 30 patients with fracture proximal humerus 2, 3 and 4-part were included in this study and were divided into 2 groups. In group 1, 15 patients were taken and were operated by deltopectoral approach, while in group 2, 15 patients were taken and operated by transdeltoid approach. All the fixation was done by PHILOS. Result: In group 1, out of 3 patients having 2-part fracture, 2 had excellent result and 1 had fair result. Out of 4 patients having 3-part fracture, 3 had good outcome and 1 had fair result. Out of 6 patients having 4-part fracture, 1 had good outcome. In group 2, out of the 3 patients having 2-part fracture, 1 had excellent outcome and 2 had good outcome. Out of the 4 patients having 3-part fracture, 1 had excellent outcome, 3 had good outcome. Out of the 6 patients having 4-part fracture, 3 had good result. Conclusions: Deltopectoral approach is recommended for calcar reconstruction that provides better visibility of medial calcar reduction while transdeltoid approach is recommended for greater tuberosity reduction that provides better visibility of greater tuberosity.